STUDY OF UTILIZATION RATE THE BASIC FACILITY IN BELAWAN OCEAN FISHING PORT REGIONS NORTH SUMATRA PROVINCE - Kamelia. A. Tambunan; Syaifuddin '; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The condition of the basic of fishery port in PPS Belawan was almost all in goodwith standard of port facilities A class. But, its better to improve its function inorder to more efficient and effective. The port of facilities consist of wharf,harbor, main port, jetty, revetment, pool and cruise lines. To know the conditionand the level of utilization in PPS Belawan the researcher conducted the researchthrough survey method. Based on the calculation technique of utilizationfacilitywas goog. Then, the land in PPS area was 54,84 ha and had built the kindsof facilities to fishing equipment further. Until now, 51,74 ha is used and theempty land area was 3,2 ha. Furthermore, the it presentation was 94,17% and itwas good criteria. This pier was made of concrete that serves the place of load andunload the fishing boats. The level of pier utilization was 327,18% with theappropriate long was 503,86 metres. The main harbor road has the 2.512 metreslong and 9 metres with the concrete construction, the total of jetty was 3 unit withsize was 48 metres long and 7 metres wide . the revetment was made of concreteconstruction 256 metres. And the pool width of harbor 22,5 ha, the cruise linewas 1.500 metres.Keywords : PPS Belawan, basic facility, study of utilization of facility